L’absence de l’anthroponyme du personnage principal dans L’effacement de Samir Toumi : représentation et/ou aliénation - Samira Ibecheninene (Multilinguales)
This article examines the unusual observation of the absence of the main character’s first name in Samir Toumi’s work titled Erasure. In contrast to the common presence of first names in fictional works, this particularity raises questions about representation and/or alienation. By analyzing this narrative choice, the study seeks to understand how the absence of the character’s first name creates a paradox compared to literary tradition, influencing the perception of the character and suggesting profound implications for the nature of storytelling. The goal is to explore whether this absence serves as a means of representation or contributes to a sense of alienation. The author’s idea regarding the first name invites readers to reflect on the implications of such a strategy. The deliberate absence of the main character’s first name prompts a reflection on the author’s narrative choices.